BOAS PRÁTICAS OBSTÉTRICAS: TERAPIA DE CALOR PERINEAL FACILITADA POR SUPORTE PARA COMPRESSAS - Melo, Andressa Avila (2020)
Introduction: Normal delivery generates benefits to the mother and child, however, about 85% of women may not remain with the intact perineum due to some perineal injury resulting from the expulsive period. There may be many complications resulting from perineal lacerations, such as: postpartum pain, bruising, edema, infections and dyspareunia. Within the broad scope of practices aligned with the humanization of childbirth, techniques for the reduction of perineal trauma in vaginal deliveries are an essential tool for efficient care. The warming of the perineal region during the expulsive period of childbirth has been reported as a non-invasive strategy that has positive effects for the reduction of spontaneous perineal lacerations. Justification: The development of a support so that compresses can be packaged and heated, which is easy to implement, has the potential to expand and facilitate the practice of heat therapy in the perineum in Brazilian maternities. In addition, it will be possible to contribute to the work process of delivery care professionals who use heated compresses and protect them from possible injuries. Objectives: To reflect on the challenges of implementing heat therapy in the perineum as a method for reducing perineal lacerations in Brazilian maternity hospitals and develop a support system to pack compresses and ensure adequate heating in an ergonomic way to implement heat therapy in the perineum, in order to reduce and / or prevent perineal lacerations. Method: This is a theoretical essay that proposes a reflection on the possible challenges faced to implement heat therapy as a method for reduction of perineal lacerations in vaginal deliveries in Brazilian maternities. In addition, a report on technological innovation was produced and its description meets the 5W2H project management process. Results: This study resulted in a theoretical survey regarding the challenges faced to implement heat in the perineum in Brazilian maternity hospitals and in the development of an intellectual property asset, called ergonomic support for heating compresses. Conclusion: Design of an ergonomic support can favor the implementation of heat therapy in the perineum in maternity hospitals throughout Brazil. In addition, it is also expected to expand future scientific production in the area. In addition, it improves the work process of birth care professionals, avoiding future ergonomic problems. The unprecedented nature of this technological product also reveals the capacity of the entrepreneurial nurse, capable of identify weaknesses and developing innovative health strategies, both for assistence care and hospital management. Technical product: Ergonomic support to pack compresses, in order to guarantee adequate heating for therapy in the perineum. It can be designated as an intellectual property asset aligned with the implementation of good obstetric practices. The support intends to qualify childbirth assistance, favoring the comfort and safety for the woman, as well as the safety of the health professional who assists her. It is an innovative product, with potential for impact and easily replicable.